RESOLVING HIGH PRECISION U-PB AGES FROM TERTIARY PLUTONS WITH COMPLEX ZIRCON SYSTEMATICS - McClelland W.C.; Mattinson J.M. (My University, 1996)
Success in establishing high precision crystallization ages with the U/Pb zircon method is highly dependent on the ability to isolate or remove the effects of inherited xenocrystic components or secondary lead-loss, or the combined effects of both. Current ''conventional'' single crystal and ion probe (SHRIMP) methods are successfully applied to Paleozoic and older samples but typically suffer from imprecision when applied to younger (Mesozoic-Cenozoic) samples due to generally reduced radiogenic lead concentrations. Here we apply a series of intense partial dissolution steps to multigrain zircon fractions from a series of Paleocene tonalitic to granodioritic intrusive rocks from southeastern Alaska. The zircon systematics are complicated by both minor inheritance and postcrystallization lead-loss. Physical and isotopic evidence demonstrate that the partial dissolution steps preferentially remove outer layers susceptible to lead loss, as well as core regions containing inherited components. The final residues are often hollow shells of low-U primary igneous zircon that yield highly precise, reproducible, and concordant ages. The resulting age determinations commonly statistically differ at the 95% confidence level from ages based on apparently concordant, but less precise conventional isotope dilution analyses, the uncertainties of which masked minor, subtle isotopic complexities. This observation strongly cautions against basing age assignments of samples yielding slightly discordant data on (1) single ''concordant'' analyses accompanied by an array of discordant data or (2) the mean of several 206Pb/238U or 207Pb/206Pb ages. The step-wise dissolution technique allows age determinations on young, relatively low U and Pb zircons at a resolution not currently possible with techniques such as single-grain conventional or spot ion probe analyses. Widespread application of the technique will likely prove instrumental in resolving detailed magmatic histories of igneous complexes where zircon systematics are typically complex.
Keywords: Mesozoic; Paleozoic; Paleocene; Cenozoic; Mesozoic; Кайнозой; Cenozoic; Мезозой; Палеозой; Кайнозой::Палеоген::Палеоцен; Paleozoic; Cenozoic::Paleogene::Paleocene